Mendelian randomization reveals plasminogen as a common therapeutic target for myocardial infarction and atrial fibrillation - Hadi Charati; Ahmad Hamta (Journal of Cardiovascular and Thoracic Research)
Introduction: Plasma proteins play essential roles in myocardial infarction (MI) and atrial fibrillation (AF) ; however, it remains unknown whether the two disorders share causal plasma proteins. Methods: The present study utilizes cis-protein quantitative trait loci (cis-pQTLs) for 4,719 plasma proteins to assess their causality on MI and AF. Results: Two-sample Mendelian randomization (MR) identifies 21 and 9 plasma proteins for MI and AF, respectively (FDR P<0.05), with plasminogen (PLG) being a commonly protective factor against both diseases. Multi-trait MR suggests that PLG is also protective against coronary atherosclerosis. PheWAS analysis identifies associations of six cis-pQTLs with both MI and AF, i.e., rs11751347 (PLG), rs11591147 (PCSK9), rs77347777 (ITIH4), rs936228 (ULK3), rs2261033 (AIF1V), and rs2711897 (BDH2). Furthermore, interactions exist among the causal plasma proteins, with PLG directly interacting with multiple others. Drug-gene databases suggest that PLG activators, such as Urokinase, Reteplase, Streptokinase, Alteplase, Anistreplase, Tenecteplase, Desmoteplase, and Defibrotide sodium may serve as common therapeutic drugs for MI and AF. Conclusion: Our study provides a causal inference of human plasma proteins in MI and AF. Several of the identified proteins and single nucleotide polymorphisms (sNPs) exert pleiotropic effects on other cardiometabolic phenotypes, indicating their crucial roles in the pathology of cardiovascular disease (CVD). Our study provides new insights into the shared causality and drugs for MI and AF.